Differential Effects of High-Protein Diets Derived from Soy and Casein on Blood-Brain Barrier Integrity in Wild-type Mice - Snelson, Matthew; Mamo, John; Lam, Virginie; Giles, Corey; Takechi, Ryu (Frontiers, 2017)
A number of studies report that a diet high in protein influences cognitive performance, but the results are inconsistent. Studies demonstrated that protein from different food sources has differential effects on cognition. It is increasingly recognized that the integrity of cerebrovascular blood-brain barrier (BBB) is pivotal for central nervous system function. However, to date, no studies have reported the effects of high-protein diets on BBB integrity. Therefore, in this study, the effects of diets enriched in casein or soy protein on BBB permeability were investigated. Immunomicroscopy analyses of cerebral parenchymal immunoglobulin G extravasation indicated significant BBB disruption in the cortex of young adult mice maintained on high-casein diet for 12?weeks, while no signs of BBB dysfunction were observed in mice fed with control or high-soy protein diet. Moreover, cortical expression of glial fibrillary acidic protein (GFAP) was significantly greater in mice fed the high-casein diet compared to control mice, indicating heightened astrocyte activation, whereas mice maintained on a soy-enriched diet showed no increase of GFAP abundance. Plasma concentrations of homocysteine were markedly greater in mice maintained on a high-casein diet in comparison to control mice. Collectively, these findings suggest that a diet enriched in casein but not soy protein may induce astrocyte activation through exaggerated BBB permeability by increased plasma homocysteine. The outcomes indicate the differential effects of protein sources on BBB and neuroinflammation, which may provide an important implication for dietary guidelines for protein supplementation.